2019
DOI: 10.1186/s13104-019-4145-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between hypoglycemia and hospital use, food insufficiency, and unstable housing conditions: a cross-sectional study among patients with type 2 diabetes in Sudan

Abstract: Objectives Hypoglycemia is associated with mortality and healthcare utilization. We aimed to assess hypoglycemia risk and Hospital use among Sudanese patients with type 2 diabetes. Results One hundred and fifty-nine patients with type 2 diabetes attending a diabetes center in Omdurman, Sudan during the period from June to September 2018were approached. A structured questionnaire based on hypoglycemia risk and Hospital use, Fasting plasma glucose (FPG) and the glycated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Gender wise, the distribution is equal in male and female. This is differed from Hyder study reported that female constitute 65.4% of the study population [17]. The majority of the participants 40.5% tend to age between 20 to 35 years old.…”
Section: Resultscontrasting
confidence: 58%
“…Gender wise, the distribution is equal in male and female. This is differed from Hyder study reported that female constitute 65.4% of the study population [17]. The majority of the participants 40.5% tend to age between 20 to 35 years old.…”
Section: Resultscontrasting
confidence: 58%